Static dielectric constants of acetonitrile/water mixtures at different temperatures and debye-hückel A and a0B parameters for activity coefficients - Gagliardi, Leonardo Gabriel (2007)
Static dielectric constants of acetonitrile/water mixtures in the whole composition range and within the temperature range from (15 to 60) °C have been measured. The values were fitted to a unique equation as a simultaneous function of temperature and acetonitrile composition. Densities of these mixtures at temperatures from (5 to 55) °C and different compositions have been collected from the literature. The complete data set was critically analyzed, the outliers were excluded, and the remaining values were also fitted to a unique equation as a function of temperature and acetonitrile composition, From the dielectric constants and densities, the activity coefficients of ions can be calculated by means of the Debye-Hückel approach, allowing the study of the ionic equilibria and determination of reference pH values or acidity constants in any acetonitrile/water mixture at any temperature within the studied range.